Has the OSCE Met Its Final Demise? Rebalancing Clinical Assessment Approaches in the Peri-Pandemic World - Malau-Aduli, Bunmi S.; Jones, Karina; Saad, Shannon; Richmond, Cassandra (Frontiers in Medicine, 2022)
The Objective Structured Clinical Examination (OSCE) has been traditionally viewed as a highly valued tool for assessing clinical competence in health professions education. However, as the OSCE typically consists of a large-scale, face-to-face assessment activity, it has been variably criticized over recent years due to the extensive resourcing and relative expense required for delivery. Importantly, due to COVID-pandemic conditions and necessary health guidelines in 2020 and 2021, logistical issues inherent with OSCE delivery were exacerbated for many institutions across the globe. As a result, alternative clinical assessment strategies were employed to gather assessment datapoints to guide decision-making regarding student progression. Now, as communities learn to “live with COVID”, health professions educators have the opportunity to consider what weight should be placed on the OSCE as a tool for clinical assessment in the peri-pandemic world. In order to elucidate this timely clinical assessment issue, this qualitative study utilized focus group discussions to explore the perceptions of 23 clinical assessment stakeholders (examiners, students, simulated patients and administrators) in relation to the future role of the traditional OSCE. Thematic analysis of the FG transcripts revealed four major themes in relation to participants' views on the future of the OSCE vis-a-vis other clinical assessments in this peri-pandemic climate. The identified themes are (a) enduring value of the OSCE; (b) OSCE tensions; (c) educational impact; and (d) the importance of programs of assessment. It is clear that the OSCE continues to play a role in clinical assessments due to its perceived fairness, standardization and ability to yield robust results. However, recent experiences have resulted in a diminishing and refining of its role alongside workplace-based assessments in the new, peri-pandemic programs of assessment. Future programs of assessment should consider the strategic positioning of the OSCE within the context of utilizing a range of tools when determining students' clinical competence.